Transformer l’eau de mer en ressource industrielle : application du procédé MSF au complexe GNL2/Z - Kridech, Dikra (My University, 2025)
The GL2/Z complex, specializing in the production and export of liquefied natural gas (LNG) from gas extracted from the Hassi R’mel field, relies on desalinated water to meet its essential industrial needs. This study analyzes a desalination method of the Multi-Stage Flash (MSF) type, implemented through five desalination units, each capable of producing 45.3 m³/h of distilled water, with a total capacity of 226.5 m³/h. Although initially efficient, these units have faced recurring technical issues since 2010, such as scaling and corrosion, reducing their efficiency and compromising water supply. This study proposes technical solutions to address these malfunctions and improve their performance, aiming to ensure stable and optimal production of desalinated water, thereby meeting the requirements of the GL2/Z complex and guaranteeing the reliability of critical industrial processes. Keywords: Desalination, MSF process, GL2/Z complex, seawater.
Keywords: Dessalement; procédé MSF; complexe GL2/Z; eau de mer